Preparation and Physicochemical Characterization of Acyclovir Cocrystals with Improved Dissolution Properties. Issue 11 (12th September 2013) - Bruni, Giovanna; Maietta, Mariarosa; Maggi, Lauretta; Mustarelli, Piercarlo; Ferrara, Chiara; Berbenni, Vittorio; Milanese, Chiara; Girella, Alessandro; Marini, Amedeo
<x xml:space="preserve">Abstract</x> Acyclovir is a well‐known antiviral agent. It can be administered in very high doses (from 200 to 1000 mg even three–four times daily). It has absorption problems mainly due to its poor solubility in water (about 0.2 g/100 mL at 25°C) and its oral bioavailability is approximately 15%–20% with a half‐life of about 3 h. To improve acyclovir solubility and/or its dissolution properties, two cocrystals of this drug were successfully produced with glutaric acid (AGA1:1) and fumaric acid (AFA1:1) as conformers, using a cogrinding method. Their effective formation was investigated by a broad range of techniques: thermal analysis, Fourier transform infrared spectroscopy, X‐ray powder diffraction, solid state nuclear magnetic resonance, and scanning electron microscopy coupled with energy dispersive X‐ray spectrometry. The water solubility of the AGA1:1 cocrystal was not improved in comparison to acyclovir, while AFA1:1 showed a slight increased solubility at equilibrium. The main difference was detected in terms of intrinsic dissolution rates (IDR). The IDR of the new phases were much faster compared with acyclovir, particularly at neutral pH. AFA1:1 showed the most rapid dissolution behavior in water; within 10 min, the drug was released completely, while just 60% of acyclovir was dissolved in 1 h. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:4079–4086, 2013